2012
DOI: 10.1111/j.1752-4598.2012.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal patterns of a saproxylic beetle,Osmoderma eremita, inMediterranean woodlands

Abstract: Dispersal patterns of a beetle inhabiting tree hollows, Osmoderma eremita (Scopoli, 1763) (Coleoptera: Cetoniidae), were studied in a cork oak (Quercus suber) woodland in central Italy, the southernmost part of its distribution range. During 2 years, we used radio telemetry to monitor dispersal of 39 free‐ranging individuals (16 males, 23 females). Telemetered beetles spent their lifetime not only inside hollow trees but also in other habitats, such as above or under the ground surface. Beetles were more activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 36 publications
4
49
1
Order By: Relevance
“…Generally dispersal abilities of the hermit beetle are very low, of the order of a few hundred metres. Radio-tracking yielded maximum flight distances of 180m (Hedin et al 2008), 700m (Dubois and Vignon 2008) and 1,504m (Chiari et al 2013). Other techniques confirmed this range of dispersal: 190m (Ranius and Hedin 2001) and 2,090m (Valainis et al 2015) with markrecapture studies, about 500m calculated with DNA markers (Oleksa et al 2013) and a maximum single flight distance of 1,454m and a maximum cumulative flight distance of 2,361m obtained with a flight mill (Dubois et al 2010).…”
Section: Species Studiedsupporting
confidence: 50%
See 1 more Smart Citation
“…Generally dispersal abilities of the hermit beetle are very low, of the order of a few hundred metres. Radio-tracking yielded maximum flight distances of 180m (Hedin et al 2008), 700m (Dubois and Vignon 2008) and 1,504m (Chiari et al 2013). Other techniques confirmed this range of dispersal: 190m (Ranius and Hedin 2001) and 2,090m (Valainis et al 2015) with markrecapture studies, about 500m calculated with DNA markers (Oleksa et al 2013) and a maximum single flight distance of 1,454m and a maximum cumulative flight distance of 2,361m obtained with a flight mill (Dubois et al 2010).…”
Section: Species Studiedsupporting
confidence: 50%
“…In contrast, in Italy, smaller populations per tree have been found and dispersing adults are exposed to a high predation rate (at least 28%) (Chiari et al 2013). According to this study, 39% of dispersing individuals reached distances of greater than 250m.…”
Section: Species Studiedmentioning
confidence: 99%
“…Two-year monitoring study carried out by Chiari et al (2013), regarding the spreading of hermit beetles in the forests of cork oak in central Italy showed that 39% of the population of this species dispersed only to 250 m. The longest migration observed was 1504 m. On a single tree was found only a few specimens in imago form. Most adults leave their tree.…”
Section: Resultsmentioning
confidence: 99%
“…imagines are attracted to sites of incorrectly assessed habitat quality, where reproduction is impossible or ineffective. Unfortunately, however, the mechanisms by which dead wood attracts saproxylic beetles are more complex, mostly because the propagation of the chemical signal depends on numerous local conditions, such as weather as well as micro-and mesoclimatic parameters (Hedgren 2007;Svensson and Larsson 2008;Chiari et al 2013). Moreover, recent studies have demonstrated the presence of an aggregating pheromone produced by the Rosalia longicorn (Žunic-Kosi et al 2017).…”
Section: Discussionmentioning
confidence: 99%